Pengaruh Media Matching Puzzle terhadap Penguaasaan Kosakata Siswa Kelas VII MTsN 05 Nganjuk (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
The Arabic language learning process at MTsN 05 Nganjuk faces several obstacles, including students' lack of vocabulary mastery, the lack of learning media in learning activities, and the conventional methods used. Matching Puzzles are one of the solutions presented by researchers to address these obstacles. The purpose of this study was to determine whether there is a difference in mastery between students in the experimental class and the control class. The approach used by researchers in this study is quantitative experiment, with a pretest-posttest design. The sampling technique used by researchers is probability random sampling, using the experimental class and the control class. The results of this study show a significant difference seen from the significance value of the independent sample t hypothesis test with a value of 0.000. Where the value of 0.000 < 0.050, it can be concluded that the Matching Puzzle learning media has an effect on improving students' vocabulary mastery in Arabic language material. The researchers' benefits and hopes for teachers include improving mastery and developing media tailored to their level, abilities, materials, and learning objectives. For students, it can encourage them to be more enthusiastic and active in understanding vocabulary. Future researchers can expand their research and explore other language skills.